How “X” Application Contributes to My Vocabulary Acquisition: A Reflective Study - Isna Tsabita Zulfa (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study was intended to reflect on how the author’s experience in using X Application (formerly Twitter) as a tool that contributed to vocabulary acquisition. Ellis (1994) defines vocabulary acquisition as the subconscious learning of a new word with no intention of learning. The study aims to explore how the features and contents of X Application facilitated the incidental vocabulary learning through extensive reading material and social interaction by the active use of the platform. The study focused on the engagement with the features such as threads, timelines and users’ interactions through replies and quoted tweets that gave exposure to encounter new words. This study used Kolb’s (1986) Experiential Learning Cycle as the primary theoretical framework. The reason was to demonstrate how one stage leads to the next, often looping back to new experiences and experimentation, showing the process of vocabulary acquisition. The Analysis used Reflective Journaling as the data source and Braun and Clarke’s (2006) Thematic Analysis Approach. The analysis focused on the author’s vocabulary acquisition process, which was identified through Kolb’s learning cycle: concrete experience, reflective observation, abstract conceptualization, and active experimentation. The data excerpts consisted of four journal entries written from the early stages of X Application until a significant change occurred in the platform. In total, there were approximately 22 vocabulary items ranging from K-pop terms and entertainment related expressions to self-improvement vocabulary, social issues, and common slang and acronyms. These words were acquired and gradually understood through different interactions within the platform, including observation, user engagement, and repeated contextual exposure. Given that the analysis was through a reflective study and based on the perspective of a single participant, the generalizability of the findings may be limited. However, it is recommended that additional participants contribute to future studies. Moreover, future researchers that is interested in similar studies could examine reflective narratives from multiple learners or focus on a specific linguistic category. Teachers could encourage learners to reflect on their digital interactions related to language use in online settings. Furthermore, educators and language practitioners could explore using social media platforms like X Application as an alternative tool for vocabulary acquisition.
Reupload File Repository 4 Juni 2026_Yudi,
Keywords: X Application Contributes; Vocabulary Acquisition